Capacity and Handover Analysis in Mobile WiMAX - Kacerginskis, E.; Narbutaite, L. (Elektronika ir Elektrotechnika, 2012)
This article analyzes mobile WiMAX network capacity and handover impact on characteristics of network QoS – sector capacity and service latency. Author designed software that was used for: sector capacity calculation for different modulation and subcarrier permutation techniques; handover simulation, evaluating generated data traffic dependencies from packet loss ratio and number of base stations. Mathematical equations were used for calculating regular and handover traffic blocking probability dependencies from traffic intensity for different channel assignment and prioritization algorithms. Ill. 16, bibl. 7, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.119.3.1357